Suberites lutkenii var. lanata ... - Morozov, Grigori; Strelkova, Natalya Anisimova; Zimina, Olga; Sabirov, Rushan (Zenodo, 2023)
Suberites lutkenii var. lanata (Fig. 2a–i 1) Material analyzed. Barents Sea, PINRO trawl survey 2006, st. T5 (70.2N, 33.399E), depth 263 m, temperature 4 °C, salinity 34.79 psu (1 specimen; KFU-LH-2/001). Barents Sea, PINRO trawl survey 2003, st. 107 (69.0015N, 43.0134E), depth 62 m, temperature 2.37 °C, salinity 34.08 psu (2 specimens; KFU-LH-2/002). Description. The larger specimen remarkably resembles the sole of the foot (Fig. 2a), 14 cm length × 6 cm wide × 1.5 cm thick. The upper surface has flattened, irregularly shaped scales or projections, above contiguous and below separated by grooves covered with a coarse sieve (Fig. 2 f–g). Surface looks and feels like fur. Hence the name (lānāta means woolly in Latin). The underside is relatively smooth and even (sponge appears to have rested on this side, when in situ). The single apical, relatively wide (~ 2 cm) osculum is surrounded by a short fringe and partitioned by a few septa (Fig. 2c). Osculum occupies the position, corresponding to the toe of foot. ... : Published as part of Morozov, Grigori, Strelkova, Natalya Anisimova, Zimina, Olga & Sabirov, Rushan, 2023, A preliminary account of the Arctic / Subarctic Suberites (Porifera: Demospongiae) fauna, pp. 50-70 in Zootaxa 5357 (1) on page 55, DOI: 10.11646/zootaxa.5357.1.2, http://zenodo.org/record/10012504 ...